“BRINCAR TODO MUNDO SABE! ”: relações interétnicas de crianças indígenas e não indígenas em uma escola municipal em Tocantinópolis (TO) - ANJOS, Mércia Cristina Borges dos (2023)
The Apinayé indigenous people, who inhabit the northern region of the state of Tocantins, interact daily with non-indigenous people in the most diverse urban environments. These interactions, to a large extent, are marked by representations and stereotypes arising from stigmas and racism, already observed about these natives in different times and spaces. Such representations, usually formulated in moments of socialization between adults and children, indigenous and non-indigenous, comprise an instigating field of sociological study, especially when we focus our attention on children. In this context, games take on a prominent place, as they are a universal language among the children participating in this research: “Everybody knows how to play! ”. That said, I emphasize that the present writing is the result of problematizations inherent to the socialization and interethnic relationships of Apinayé indigenous children enrolled at the Alto da Colina Municipal School in Tocantinópolis (TO). My main objective is to analyze the socialization processes and social interactions established by indigenous and non-indigenous children in the educational institution of the referred municipality and in the correlated spaces. The discussion is supported by: 1 – previous studies that address the history of the Apinayé People, the social representations of this people, and their interactions with non-indigenous people in an urban context, considering the existence of conflicting relationships (marked by stigma and racism) and mutual collaboration resulting from these interactions; and 2 – data obtained through ethnographic observations, in the school context during the year 2022. Among the main authors used in this work, I highlight: Gonçalves (1980); DaMatta (1976); Silva Apinagé (2020); Giraldin (2000); Conceição and Torres (2021); Freire (2000); Durkheim (2011); Sousa (2017); Fernandes (2016); Cohn (2005); and others. For the developed analysis, I used ethnography as a methodological proposal, with participant observation in the aforementioned municipal educational institution and in the correlated spaces, according to the readings of the authors mentioned here. From this analysis, based on observations and interactions with children, I considered that there are different representations in the school environment. While playing, talking, studying and interacting in different ways, indigenous and non-indigenous children socialize respectfully, without phenotypic and/or cultural demarcations, which points to a distancing from the stigmas and racism evidenced in the relationships between adults of different ethnicities and cultures. This reflects a section between the adult and child universes with regard to the construction and development of social relationships, as well as their consequences for the sociocultural formation of the Brazilian people.